The effect of adaptive planning on target and critical structures during radiation treatment for locally advanced lung cancer - Çağlar, Hale; Küçükmorkoç, Esra; Altınok, Ayşe; Küçük, Nadir; Doyuran, Mine; Acar, Hilal (Elsevier Science, 2015)
[Abstract Not Available]
WOS: 000370365102148
Keywords: Adaptive; Radiotherapy Planning; Lung Cancer